Thiết kế hệ thống điều khiển số tối ưu bền vững với phản hồi đầu ra - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper considers the problem of designing quadratic optimal digital control systems with uncertain parameters. For  the output feedback systems a parametric optimization technique is used.  A method for computing the  supremum of a quadratic forme is proposed. The stability of the  closed-loop systems is also discussed.